1998
DOI: 10.1073/pnas.95.22.13284
|View full text |Cite
|
Sign up to set email alerts
|

Role of brain allopregnanolone in the plasticity of γ-aminobutyric acid type A receptor in rat brain during pregnancy and after delivery

Abstract: The relation between changes in brain and plasma concentrations of neurosteroids and the function and structure of ␥-aminobutyric acid type A (GABA A ) receptors in the brain during pregnancy and after delivery was investigated in rats. In contrast with plasma, where all steroids increased in parallel, the kinetics of changes in the cerebrocortical concentrations of progesterone, allopregnanolone (AP), and allotetrahydrodeoxycorticosterone (THDOC) diverged during pregnancy. Progesterone was already maximally i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
297
3
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(314 citation statements)
references
References 34 publications
12
297
3
2
Order By: Relevance
“…Different studies have reported levels of THDOC and THP in human and rodent plasma using gas chromatography chemical ionization mass spectrometry (GC-MS) or radioimmunassays [50][51][52][53][54][55]. Using our LC-MS/MS, we were unable to detect these analytes.…”
Section: Discussionmentioning
confidence: 73%
“…Different studies have reported levels of THDOC and THP in human and rodent plasma using gas chromatography chemical ionization mass spectrometry (GC-MS) or radioimmunassays [50][51][52][53][54][55]. Using our LC-MS/MS, we were unable to detect these analytes.…”
Section: Discussionmentioning
confidence: 73%
“…With respect to the hypothalamus, allopregnanolone levels were also shown to vary across the estrous cycle, but, in contrast to cortex, the lowest levels were reported on the evening of proestrus (~40 pg/mg protein) and the highest levels during the morning of diestrus I (~95 pg/mg protein) (Genazzani et al, 1995). The differences in concentrations of progestin-and testosterone-derived neurosteroids as a function of hormonal state contrasts with that for THDOC which shows only a small increase from ~1.5 ng/g during estrus to ~ 3ng/g in late pregnancy (Concas et al, 1998).…”
Section: Neurosteroid and Anabolic Androgenic Steroid Levels In The Cnsmentioning
confidence: 78%
“…Using this methodology, allopregnanolone concentrations in cortical homogenates were estimated to be ~1-2 ng/g in juvenile, ~1 ng/g in diestrous, 4-6 ng/g in estrous, and 4-8 ng/g in proestrous females, with levels reaching ~10-30 ng/g during pregnancy (Paul and Purdy, 1992;Corpéchot et al, 1993;Concas et al, 1998;Kellogg and Frye, 1999). These assessments have been used to estimate that allopregnanolone levels are diestrus females (Paul and Purdy, 1992), but can reach ~100 nM during the late stages of pregnancy (see for example; Brussaard et al, 1997;Lambert et al, 2003).…”
Section: Neurosteroid and Anabolic Androgenic Steroid Levels In The Cnsmentioning
confidence: 99%
“…It was administered subcutaneously in a 2 ml/kg suspension of finasteride in 20% (w/ v) 2-hydroxypropyl-␤-cyclodextrin (HCD) (Research Biochemicals, Natick, M A) at either a 25 or 50 mg / kg dose. Doses of finasteride were determined by review of finasteride use in previous behavioral and biochemical experiments in rodents (Lephart et al, 1996;Concas et al, 1998;Kokate et al, 1999). Finasteride (50 mg / kg, s.c.) alters open field behavior in pregnant females rats and decreased enzyme activity by 60 -80% (Lephart et al, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…3␣,5␣-THP is an endogenous pregnane steroid and potent agonist modulator of the inhibitory neurotransmitter GABA A receptor subtype. 3␣,5␣-THP is increased in brain in many stress paradigms (Purdy et al, 1991;Barbaccia et al, 1996;Barbaccia et al, 1997), as well as during naturally occurring hormonal fluctuations such as the estrus cycle (Ichikawa et al, 1974;Paul and Purdy, 1992;Finn and Gee, 1993) and pregnancy (Concas et al, 1998). A wealth of evidence demonstrates that the anxiolytic, sedative/ hypnotic, and anticonvulsant effects attributed to 3␣,5␣-THP are mediated by enhancement of chloride ion conductance through GABA A receptors in brain (Morrow, 1995).…”
Section: Abstract: Neuroactive Steroids; Ethanol; Allopregnanolone; mentioning
confidence: 99%